Simulation and modeling of an improved multi-verse optimization algorithm for QoS-aware web service composition with service level agreements in the cloud environments - Yaghoubi, Mohamadali; Maroosi, Ali (Simulation modelling practice and theory, 2020)
•Original multi-verse optimization algorithm is a promising optimization algorithm•To improve diversity the wormholes process rate decreased in the first stages.•An adaptive traveling distance rate (TR) is proposed to adaptively adjust TR•The adaptive algorithm was adopted for the web service composition problem•Proposed algorithm outperforms others in web service composition. Cloud computing is a new trend in information technology that provides resources and shares services by web services over the internet for users. Many web services have similar functionality with different quality of service (QoS) in the cloud. Thus, an appropriate service composition method is needed to assign an optimal composition of services to the users. Furthermore, service level agreement (SLA) which is the level of service expected from the service provider should be satisfied by the service composition method that less considered in previous studies. Introducing an appropriate algorithm for web service composition that could achieve high QoS while satisfying SLA constrains is one of the main issues in the cloud computing area. In this study, an improved multi-verse optimization algorithm for web service composition that is called IMVO algorithm is proposed to improve QoS while satisfying SLA. The simulation results show increasing of normalized QoS up to 57% in comparison with the other approaches, especially for service composition problems with SLA.